Mathematical thinking ability of informatics students based on gender in calculus course - Triana Harmini; Aziz Musthofa; Shoffin Nahwa Utama (International Journal on Teaching and Learning Mathematics, 2019)
This study aimed to analyse the difference in the mathematical thinking abilities of Informatics Engineering students based on gender in Calculus problem-solving. Mathematical thinking ability was measured based on four indicators of the mathematical thinking process, namely specialisation, generalising, conjecturing, and convincing. The instruments in this study were mathematical thinking tests and observation sheets. The test used in this study was composed of four questions by indicators of the mathematical thinking process.  The technique of data collection was the test, observation, and interview. Subjects of this study consisted of 35 male students and 22 female students. Data were analysed using the t-test. The results of the analysis showed that there is a significant difference in the mathematical thinking ability of male and female students. Mathematical thinking abilities of female students reached indicators of specialisation, generalising, and conjecturing. On the other hand,  mathematical thinking abilities of male students passed the elements of speciality and generalising.